Studi Pengaruh Fasilitas Penyeberangan Terhadap Kenyamanan Pejalan Kaki Di Kawasan Simpang Lima Kota Semarang - Muhammad Bagus Pamungkas; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2023)
The existence of pedestrian crossing facilities is vital for urban areas, crossing facilities are things that can affect comfort in terms of security and safety. Simpang Lima which is a core part of city activities certainly has a very varied and many variety of movement activities. In that case, the availability of facilities such as crossing the Simpang Lima area to meet the needs of pedestrians is very important. This study aims to see the effect of the availability of pedestrian crossing facilities on the perception of pedestrian comfort.The method used is quantitative with the analysis stage, calculating vehicle/pedestrian conflict with the empirical formula PV2, then analyzing the respondents' comfort perception on the condition of the existing crossing facilities and crossing activities, then doing a correlation test and looking for the effect using the Crosstab method and regression equation model. linear, the last one performs an analysis of the choice of crossing facilities.This study found that there was a discrepancy between the results of the calculation of vehicle/pedestrian conflicts with the provision of existing facilities, so that the results of the respondents' sense of responsiveness also showed poor scores for crossing facilities in the Simpang Lima area. The two data have a relationship with each other which is proven in the results of the accepted hypothesis test, thus based on the pedestrian comfort response, it requires a type of crossing facility in the form of a Zebra Cross.